1997
DOI: 10.1093/jaoac/80.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Visual Immunoprecipitate Assay (VIP) for Listeria monocytogenes and Related Listeria Species Detection in Selected Foods: Collaborative Study

Abstract: Six foods representing a variety of food products were analyzed by the Assurance Listeria polyclonal enzyme immunoassay (EIA) and by either the Bacteriological Analytical Manual or the U.S. Department of Agriculture culture method for detecting Listeria monocytogenes and related Listeria species. Samples of each food type, at each inoculation level, were analyzed simultaneously by both methods. A total of 19 laboratories representing federal government agencies and private industry in the United States and Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The results of this study are different from those of Feldsine et al (1997). They found that the VIP was more efficient to detect Listeria sp.…”
Section: Resultscontrasting
confidence: 99%
“…The results of this study are different from those of Feldsine et al (1997). They found that the VIP was more efficient to detect Listeria sp.…”
Section: Resultscontrasting
confidence: 99%